2020
DOI: 10.1097/md.0000000000022076
|View full text |Cite
|
Sign up to set email alerts
|

Use of steroids to treat anti-tumor necrosis factor α induced tuberculosis-associated immune reconstitution inflammatory syndrome

Abstract: Introduction: Individuals with tuberculosis (TB) who are being treated with anti-tumor necrosis factor α (anti-TNFα) for coexisting conditions may experience unexpected exacerbations of TB after the initiation of antituberculous therapy, so-called anti-TNFα-induced TB-immune reconstitution inflammatory syndrome (anti-TNFα-induced TB-IRIS). Anti-TNFα-induced TB-IRIS is often treated empirically with corticosteroids; however, the evidence of the effectiveness of corticosteroids is lacking and the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Toluidine blue play s a profound role in the field of medicine. It can be used as a nucleic acid dye for the detection of tumors in a clinic setting, 17 , 18 and as a safe and effective photosensitive material for both PDT and PTT. 19 However, it is aggregates easily at high concentrations, and the generation of polymers affects the photosensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…Toluidine blue play s a profound role in the field of medicine. It can be used as a nucleic acid dye for the detection of tumors in a clinic setting, 17 , 18 and as a safe and effective photosensitive material for both PDT and PTT. 19 However, it is aggregates easily at high concentrations, and the generation of polymers affects the photosensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…The cases of anti-TNF–associated tuberculosis-IRIS have often been reported [ 2 ], whereas those of anti-TNF–associated NTM-IRIS are rare. In a previous case series of 13 patients with anti-TNF–associated NTM pulmonary disease, no patient was IRIS [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Steroid dosage was increased, and treatment was subsequently completed [ 10 ]. Although the number of cases of anti-TNF–associated NTM-IRIS is insufficient, the clinical presentation of such patients might be mild compared to that of patients with anti-TNF–associated tuberculosis-IRIS [ 2 ]. Some of the patients from the reviewed case reports and the present patient had received cytotoxic drugs in addition to TNF inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that Tropheryma whipplei exerts suppression on CD4+ T-cells and the syndrome can develop after antibiotic medication [ 20 ]. Glucocorticoids are drugs of choice in patients with immune reconstitution inflammatory syndrome [ 56 ].…”
Section: Treatmentmentioning
confidence: 99%